Adolescents’ Memories of Career Information Videotapes - Lapadat, Judith; Martin, Jack; Clarkson, Nancy (Canadian Journal of Counselling and Psychotherapy, 1993)
The theory of memory-mediated learning proposed by Martin (1989; 1990; 1991, in press), following Tulving (1983, 1985), and Paivio (1986), emphasizes the role of learners' experiential, episodic memories as mediators between psycho-educational interventions and learners' everyday application of what they have learned from such interventions. We used this theory as a basis for examining what adolescents remember from viewing videotapes intended to provide information about specific careers to high school students. We compared two videotaped career presentations to find out whether students differed in their memories of, and responses to the information presented. One tape was produced with the explicit intent of enhancing visual and experiential content. The other is widely used in counselling centres across Canada. Findings were that although students expressed a reliable preference for the former, there were no reliable differences in number of visual or verbal memories reported for each tape, or in accuracy of content recalled. An anticipated link between affective information and a visually enhanced medium was supported, but other predictions of the theory of memory mediation were not. A practical implication is that either videotape was equally effective in promoting students' learning of facts about a career, between affective information and a visually enhanced medium was supported, but other predictions of the theory of memory mediation were not. A practical implication is that either videotape was equally effective in promoting students' learning of facts about a career, despite their expressed preferences for one videotaped presentation over the other.